First observations of polarized scattering over ice clouds at close‐to‐millimeter wavelengths (157 GHz) with MADRAS on board the Megha‐Tropiques mission. Issue 21 (14th November 2014) - Defer, Eric; Galligani, Victoria S.; Prigent, Catherine; Jimenez, Carlos
Abstract: Polarized scattering by frozen hydrometeors is investigated for the first time up to 157 GHz, based on the passive microwave observations of the Microwave Analysis and Detection of Rain and Atmospheric Structures (MADRAS) instrument on board the Indo‐French Megha‐Tropiques satellite mission. A comparison with time‐coincident Tropical Rainfall Measurement Mission Microwave Imager records confirms the consistency of the coincident observations collected independently by the two instruments up to 89 GHz. The MADRAS noise levels of 1.2 K at 89 GHz and of 2.5 K at 157 GHz are in agreement with the required specifications of the mission. Compared to the 89 GHz polarized channels that mainly sense large ice particles (snow and graupel), the 157 GHz polarized channel is sensitive to smaller particles and provides additional information on the cloud systems. The analysis of the radiometric signal at 157 GHz reveals that the ice scattering can induce a polarization difference of the order of 10 K at that frequency. Based on radiative transfer modeling the specific signature is interpreted as the effect of mainly horizontally oriented ice cloud particles. This suggests that the effects of the cloud particle orientation should be considered in rain and cloud retrievals using passive radiometry at microwave and millimeter wavelengths. Key Points: Cloud scattering induces polarization difference of the order of 10 K at 157 GHz Particle orientation must be considered in rain and cloud microwave retrievals MADRAS radiometric sensitivities at 89 GHz and 157 GHz are below 1.2 K and 2.5 K